Isolation of cis-Zeatin from Corynebacterium fascians Cultures - Scarbrough, Emanuel (1973)
Three cytokinin-active constituents have been isolated from the culture medium of Corynebacterium fascians, a plant pathogen causing fasciation. One constituent is now identified as cis-zeatin [6-(4-hydroxy-3-methyl-cis-2-butenylamino)purine]. It represents the first unequivocal demonstration of the production of a zeatin isomer by a bacterial species. Another constituent was identified earlier as 6-(3-methyl-2-butenyl-amino)purine. The third constituent, distinct, on Sephadex LH-20 column chromatography, from the above two and their ribosides, has not yet been identified.